Strategic Planning for Trang Province Health System Development for the Year 2007-2011 - Akkharasuwankul, Anan (Journal of Health Science of Thailand, 2017)
This participatory action research was in relation with the bureaucracy system reform, the health system reform and the Act concerning principles and methods of good governance, 2546 B.E. The study was carried out through workshops of academics and administrators in all stages of the process, SWOT analysis, strategic planning, bringing the strategic plan into practice, controlling, monitoring and evaluating the implementation of the strategic plan and the opinion survey for evaluating the strategic planning process. The vision of the Office of Trang Provincial Public Health was าTo be the office with an effective administration system to support the health service to help Trang people live happily together by the year 2011ำ. Three missions were identified: 1) to develop the administration system, 2) to support the health service system, and 3) to support good health establishment of health alliance and public sector. Four goals were established: 1) Trang people lived happily together, 2) the office had high qualities and standards, 3) the health alliance participates in establishing good health, and 4) the office has an effective administration system. The implementation was driven by 7 strategies: 1) supporting good health establishment, 2) developing the primary health service system, 3) developing the control system of health disasters, 4) developing the administration system, 5) developing the information technology and communication system, 6) developing the knowledge management system, and 7) developing health manpower. The methods of bringing the strategic plan into practice included making the annual action plan, subsidizing the implementation of the strategic plan, making the official contract, creating the motivation system, establishing a strategic plan administration committee for controlling and monitoring, developing a cockpit-management public health center, and evaluating the implementation of the strategic plan by the self-assessment report (SAR), and the health service network certification of the provincial inspectors. With reference to the survey results, 71 academics and administrators (95% of the target group) thought that the strategic planning for Trang province health system development of the year 2007-2011 was appropriate at a fair level. It was expected that all sections would rely on the strategic planning system of the Office of Trang Provincial Public Health in its thrive toward effective implementation to achieve the goals